MBKM (Merdeka Belajar Kampus Merdeka) Under Jambi University’s Arabic Education Program during the Industrial Revolution: Implementation, Supporting and Inhibiting Factors (Version 4.0) - Muid, Abdul; Ilhami, Rosita; Febriani, Suci Ramadhanti (Institut Agama Islam Negeri Curup, 2022)
This study aims to determine the implementation, supporting, and inhibiting factors for the MBKM program in the Arabic Language Education Study Program, Jambi University. The Ministry of Education and Culture has initiated a new university program, namely Merdeka Belajar Kampus Merdeka (MBKM) to prepare superior and competitive human resources in the 4.0 revolution era. The research method employs field research, which includes qualitative research. Research data collected from primary data and secondary data sources and the data collection techniques using documentation, observation and interviews. This research uses the process of data reduction, data presentation, and conclusions to analyze the data. The finding shows that: 1) the implementation of MBKM at the Jambi university is still not going well because it still finds confusion in the process, so it is necessary needs adaptations related to the curriculum and facilities, 2) the supporting factors are the willingness and enthusiasm of the educators and students as seen from their cohesiveness in preparing for the establishment of MBKM, while 3) the inhibiting factor is the need to get a lot of MoU from various institutions. In addition, there are other challenges, namely the readiness and skills of students to teach and guide in schools. This means that students must be part of strengthening learning and numeracy.